Optimization of the Photochemical Degradation of Textile Dye Industrial Wastewaters - T.H. Dang; T.P. Mai; M.T. Truong; L.T Dao; T.A.N Nguyen (Universitas Gadjah Mada, 2016)
In this study, the photochemical degradation via photo-Fenton process was carried out to degrade dyes in textile industrial wastewaters. Experimental design methodology was also applied for optimizing effects of factors which influencethe effective treatment such as ferric dose, hydroperoxide dosage, initial pH, reaction time and initial chemical oxygen demand (COD). Two independent variables namely colour and COD removal efficiencieswere used to evaluate the treatment yield. Under the optimal conditions, ca. 99% and ca. 88%, colour, and COD were removed, respectively.